Prevalence and Intensity of Human Schistosomiasis in Selected Communities of Ibi Local Government Area, Taraba State, Nigeria - D, Rimamsomte; J, Agere H. I; M, Dawuda; K, Mijah A.; Jerry, J. T (Darul Yasin Al Sys, 2026)
This study determined the prevalence and intensity of Schistosoma haematobium infection among residents of selected communities in Ibi Local Government Area (LGA), Taraba State, Nigeria. A total of 400 urine samples were randomly collected from residents aged 6 years and above, across five communities (Ibi, Rafin Soja, Gindin Waya, Ando Manu, and Nwukam). Urine sedimentation technique was employed for parasite detection, and infection intensity was expressed as mean egg count per 10 ml of urine. Data were analysed using SPSS version 26, and associations between variables were tested using Chi-square (χ²) at a 5% significance level. The overall prevalence of S. haematobium infection was 7.5%, with a mean egg intensity of 2.2 eggs/10 ml of urine, indicating a low level of endemicity. Gindin Waya recorded the highest prevalence (12.5%) and intensity (2.4 eggs/10 ml), while Ibi had the lowest (2.5%; 1.0 egg/10 ml). Infection was most common among the 16–25-year age group (9.1%) and males (9.0%), although differences by age (χ² = 2.157, p = 0.707) and sex (χ² = 1.489, p = 0.222) were not statistically significant. Farmers (8.3%) and fishermen (7.5%) had higher infection rates than other occupations (χ² = 3.295, p = 0.509). A significant association was observed between infection and water source (χ² = 7.935, p = 0.0475), with river and stream users showing higher prevalence. The persistence of urinary schistosomiasis, despite low infection intensity, indicates ongoing transmission within riverine communities. Continuous mass drug administration, improved access to safe water, snail vector control, and community health education are recommended to reduce transmission and achieve WHO’s 2030 schistosomiasis elimination target.